ANALISIS HUBUNGAN FAKTOR DEMOGRAFI, FAKTOR PENYAKIT, DAN FAKTOR PSIKOLOGIS DENGAN MAKNA SPIRITUAL PENGALAMAN SAKIT - Nurhayati Nurhayati; Rohman Azzam; Mustikasari Mustikasari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
ABSTRACT The prevalence of HIV/AIDS is increasing in almost all over the world, the most incidence is in productive age. High community stigma and discrimination, has a negative impact on people living with HIV/AIDS (PLWHA) and the wider life. Objective: Identify the relationship between demographic factors (age, gender, latest education, occupation, religion, economic status, marital status), disease factors (initial diagnosis, opportunistic infections, medication adherence), and psychological factors (anxiety and depression) with meaning, spiritual experience of illness in PLHIV in East Jakarta. This study used a cross sectional study design with consecutive sampling involving 225 respondents at the Bhayangkara Hospital Level I R. Said Sukanto, Jakarta. The independent t test obtained the age factor with a p value of 0.043, meaning that there was a relationship between age and the spiritual meaning of the experience of illness. Chi square test on the factors of gender, recent education, employment, religion, economic status, marital status, early diagnosis, opportunistic infections, adherence to taking medication, anxiety and depression obtained p value> 0.05 means that there is no relationship between these factors and meaning, spiritual experience of illness. Opportunistic infection is a dominant factor related to the spiritual meaning of the experience of illness. There is a relationship between age and the spiritual meaning of the experience of illness, and opportunistic infections are the dominant factor related to the spiritual meaning of the experience of pain. Suggestion: It is necessary to do further research based on initial diagnosis or duration of HIV infection.